Analisis Return Portfolio Saham Berbasis Market Capitalization, Dividend, Net Profit Margin, dan Debt To Equity Ratio - Natashia, Natashia (Keizai, 2024)
Investors always aim for high returns on their investments. Proper analysis is crucial as it affects the returns they receive. This analysis not only evaluates a company's prospects but also helps in building a portfolio. Many experts suggest not putting all money into one type of investment. When creating a portfolio, both return and risk must be considered. Recently, many people have shared simple portfolio-building strategies to help young investors with limited investment knowledge. This study examines whether portfolio returns based on influencer investment strategies are higher than the IDX Composite (IHSG) returns. Using a sample of 910 companies from 2021 and 2022, the researcher filtered fundamental data and identified 23 eligible companies in 2021 and 25 in 2022. After forming the portfolio, an independent sample t-test was conducted. The results show that the portfolio's return is higher than the IHSG return.